Costuming the Shakespearean stage : visual codes of representation in early modern theatre and culture - Lublin, Robert I. (Studies in performance and early modern drama., 2011)
What was worn on the Shakespearean stage and more importantly, how were articles of apparel understood when seen by contemporary audiences? Considering royal proclamations, religious writings, paintings, woodcuts, plays, historical accounts, sermons and legal documents of early modern England, Robert Lublin investigates what Shakespearean actors actually wore in production as well as what cultural information was conveyed by those costumes. -- Provided by publisher.